2017
DOI: 10.1007/s00425-017-2794-5
|View full text |Cite
|
Sign up to set email alerts
|

Funaria hygrometrica Hedw. elevated tolerance to D2O: its use for the production of highly deuterated metabolites

Abstract: The method introduced here to grow F. hygrometrica in high concentrations of D O is an excellent alternative to produce highly deuterated metabolites with broad applications in metabolic studies. Our mass spectrometry experiments strongly indicate the successful incorporation of deuterium into organic compounds. Deuterated metabolites are useful tracers for metabolic studies, yet their wide utilization in research is limited by the multi-step total synthesis required to produce them in the laboratory. Alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Exceptions exist, and so, Vergara et al. used water moss F. hygrometrica at high D 2 O concentrations (90 %) to isolate deuterated chemicals . In addition, heavy water inhibited human pancreatic tumor cells in vitro…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Exceptions exist, and so, Vergara et al. used water moss F. hygrometrica at high D 2 O concentrations (90 %) to isolate deuterated chemicals . In addition, heavy water inhibited human pancreatic tumor cells in vitro…”
Section: Figurementioning
confidence: 99%
“…[16] Exceptions exist, and so, Vergara et al used water moss F. hygrometrica at high D 2 O concentrations (90 %) to isolate deuterated chemicals. [17] In addition, heavy water inhibited human pancreatic tumor cells in vitro. [18] Electrochemical [19] and gravimetric [20,21] DNA biosensors have been frequently examined.…”
Section: Voltammetric H/d Isotope Effects On Redox-active Small Molecmentioning
confidence: 99%
“…In fact, the cell-free assay of GFP expression carried out by Hohlefelder et al which have shown a considerable H/D isotope effect, give an indication of antiproliferative properties of heavy water [14] . Exceptions exist, and so, Vergara et al could use water moss F. hygrometrica in high concentrations (90%) of D2O to isolate deuterated chemicals [15] . Heavy water showed an inhibiting effect upon human pancreatic tumor cells in vitro [16] .…”
Section: Introductionmentioning
confidence: 99%